Vendégelégedettség mérés a mórahalmi Thermal panzióban - Marosi, Tibor; Bitófalvi, Dóra (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
Thermal Pension was founded in 2002, as the first commercial accommodation of Mórahalom, and has worked effectively ever since. The main advantage of the Pension is the central location, the direct connection to Szent Erzsébet Spa and to the catering service. Furthermore the trained and skilled personnel and the related services are dominant factors. In this paper partly the guest traffic of the region was studied, moreover an assessment was done about the services of Thermal Pension. An evaluation of customer satisfaction was accomplished, applying a questionnaire survey combined with personal interview in some cases. Approximately hundred evaluable questionnaires were processed. The results indicate that the guest number increased steadily in the past decade. In this period the number of private and public accommodation also increased. The overall satisfaction with the Pension is high, 98% of surveyed responded that they would come again, and would recommend the Pension to their friends and acquaintances. The strength of the Pension is the friendly and familiar atmosphere, the kindness and helpfulness of the staff. From the analysis of the open-ended questions guests have reported satisfaction with the corresponding expectations. Around 30% of the surveyed were uncomfortable because of the noise of road traffic. In the future the Pension should pay more attention to this remark.